Comparing Carbon Stock and Increment Estimation using Destructive Sampling and Inventory Guideline of Acacia Catechu, Dalbergia Sissoo, Eucalyptus Camaldulensis and Pylunthus emblica Plantations, Mahottary Nepal - Mandal, Ram Asheshwar; Dutta, Ishwar Chandra; Jha, Pramod Kumar (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2017)
This research was objectively carried out to compare the forest carbon stock estimation and increment applying destructive sampling and community forest inventory guideline (CFIG). Plantation of Acacia catechu, Dalbergia sissoo, Eucalyptus camaldulensis and Pylunthus emblica at Pragatinagar community forest, Mahottary Nepal was selected for this study. Altogether 62 random points were distributed to select the plant applying stratified random sampling for harvesting purpose. The diameter and height of plants were recorded and these were uprooted. Total 192 discs were slashed each from stem and branches and eight discs cut from the root of plants. The samples were dried in lab. The carbon stock and mean annual carbon increment (MACI) were calculated using both methods to compare the values statistically. The moisture content was about 45.34% in leaves of Eucalyptus camaldulensis and there was about 51 – 58% contribution of stem in total carbon of Pylunthus emblica. Total carbon stock was 3.61±1.32 t/plant of Acacia catechu applying destructive sampling which was 5.37±0.88 t/plant using CFIG and the MACI was 0.72 t/plant of same species using destructive sampling which was 1.07 t/plant using CFIG. The t-test showed significance difference in values of carbon stocks and MACIs at 95% confidence level employing the methods.